Conundrum of religious mafia and legislation in South Africa: When does religion become a national threat? Reference to the Seven Angels Ministry - Dube, Bekithemba (Verbum et ecclesia, 2019)
In this theoretical article, I analyse the hearing of the Seven Angels Ministry before the Commission for Religious and Linguistic Rights, and subsequent events that led to the killing of police and army officers at the Ngcobo Police Station. Informed by critical emancipatory research theory, I unpack the emerging nexus of the state, gender, legislation, religious freedom and human rights in the context of religious mafia. I answer two questions in relation to the Seven Angels Ministry and the Ngcobo killings: 'What are the tenets of a mafiarised religion?' and 'What can be done to mitigate the challenge?' I argue that a philosophical understanding of the constitution, education, gender and politics as practiced by the Seven Angels Ministry presents a trajectory of religion in contemporary society that must be problematised, unearthed and challenged to produce a world order that is responsive to societal needs and devoid of oppression and coloniality. I also argue that while religious freedom is a human right, it is important that legislation protects citizens from religious mafias, particularly when religious discourses negate schooling, promote gender inequality and emphasise constitutional delinquency.Intradisciplinary and/or interdisciplinary implications: The article is interdisciplinary in the sense that it addresses the issues of education, constitutionalism, gender, child abuse and a need for a theology that challenges religious mafia exhibited by some religious movements. It calls for a change in legislation, and a different approach to theology as well as in curricula to address lived realities.